THE MULTIFUNCTIONALITY OF FARMS RUN BY FARMERS-ENTREPRENEURS - Zając, Dariusz (Acta Scientiarum Polonorum. Oeconomia, 2010)
The paper makes assessment of farmers-entrepreneur’s efforts to undertake new ventures as a part of implementation of the multifunctional model of agriculture. The research has proved that apart from non-agricultural activities more than half of the farmers-entrepreneur’s have already undertaken other forms of multifunctional activities. Among the most popular are a direct sale of in-farm made products and participation in agricultural programmes in favour of environmental protection. The level of farmers-entrepreneur’s involvement in this range depends on their age and education, the area and economic size of farm, the kind of already run non-agricultural activity and its importance for family’s income as well as the intensity of theirs relations (cooperation) with local institutions.